Longitudinal associations between PACAP plasma concentration and symptoms of post-traumatic stress and depression in South African rape-exposed women - Kapp, Lianna Kaycee (Stellenbosch : Stellenbosch University, 2023)
Kapp, Lianna Kaycee. 2023. Longitudinal associations between PACAP plasma concentration and symptoms of post-traumatic stress and depression in South African rape-exposed women. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/7e66290a-591e-4237-ac05-8d71e8197e29